Pseudo-Hippocratic Zodiacal Lunaries in the Hunterian Collection: A Comparative Study of the Manuscript Context of Glasgow University Library Hunter MS 461 and Hunter MS 513 - Irene Diego Rodríguez (SELIM)
Manuscript catalogues are rarely comprehensive. Thus, brief texts and/or treatises incorporated by later hands may have gone unnoticed. This is the case of two medieval manuscripts housed at Glasgow University Library—Hunter MS 461 and Hunter MS 513—which contain the same medical astrological tract, known as Astrologia Ypocratis in Latin or Þe boke of ypocras in English. Hunter MS 461 is an astrological and mathematical compendium written mainly in Latin in the thirteenth century and Hunter MS 513 is a medical miscellany in English dating from the fifteenth century. Close and direct reexamination of the contents gathered in both medieval manuscripts will uncover treatises, notes and later insertions which have passed unperceived by the eyes of scholarship so far. This study will provide a more detailed map of the context in which the medical astrological tract under consideration was copied during the Middle Ages and will also offer some new insights regarding the evolution of the status this tract enjoyed from the thirteenth to the fifteenth centuries.